Environmental Performance, Kepemilikan Manajerial, Leverage, Profitabilitas dan Pengungkapan Corporate Social Responsibility - Merdekawati, Mega Ayu; Azizah, Siti Nur; Santoso, Suryo Budi; Hapsari, Ira (E-Jurnal Akuntansi, 2022)
The trend of CSR implementation changed when the pandemic started. The research aims to empirically re-examine the effect of environmental performance, managerial ownership, leverage and profitability on CSR disclosure in line with the agency, stakeholder and legitimacy theories. The object of research is the energy sector companies on the IDX with a population of 229 companies for the 2019-2021 period. The sample obtained is 131 observational data obtained by purposive sampling technique. The results of the study show that environmental performance and leverage have a positive effect. Research also proves that managerial ownership and profitability have no effect on disclosure of corporate social responsibility. Keywords: Environmental Performance; Managerial Ownership; Leverage; Profitabilitas; Corporate Social Responsibility.